2015
DOI: 10.1007/s10973-015-4526-z
|View full text |Cite
|
Sign up to set email alerts
|

Use of high-resolution thermogravimetric analysis (HRTG) technique in spent FCC catalyst/Portland cement pastes

Abstract: Thermogravimetric analysis (TG) is one of the most common instrumental techniques used for the characterization of pastes, mortars and concretes based on both calcium hydroxide or Portland cement.Important information about pozzolanic materials can be assessed concerning to calcium hydroxide consumption and the formation of new hydrated products. Nevertheless, in some cases, problems associated to the overlapped decomposition processes for hydrates difficult the analysis of obtained data.In this paper the use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…As evidenced in the table, many overlaps are present among the thermal processes relative to the clay minerals and those of the zeolites, causing some ambiguities in the interpretation of the peaks. The results of the TG analysis after one year of curing, and the first derivative of the TG curves (DTG), are reported in Figure 11, while in Table 3, the ranges of temperature relative to the main transformations are reported [80][81][82][83][84][85][86][87][88][89][90]. As evidenced in the table, many overlaps are present among the thermal processes relative to the clay minerals and those of the zeolites, causing some ambiguities in the interpretation of the peaks.…”
Section: Presence Of New Phases and Residues Of The Original Additives In The Separated Clay Fractionmentioning
confidence: 99%
“…As evidenced in the table, many overlaps are present among the thermal processes relative to the clay minerals and those of the zeolites, causing some ambiguities in the interpretation of the peaks. The results of the TG analysis after one year of curing, and the first derivative of the TG curves (DTG), are reported in Figure 11, while in Table 3, the ranges of temperature relative to the main transformations are reported [80][81][82][83][84][85][86][87][88][89][90]. As evidenced in the table, many overlaps are present among the thermal processes relative to the clay minerals and those of the zeolites, causing some ambiguities in the interpretation of the peaks.…”
Section: Presence Of New Phases and Residues Of The Original Additives In The Separated Clay Fractionmentioning
confidence: 99%
“…This process was followed with weight loss of about 0.65% in the temperature range 25-400 • C. In the second temperature interval (400-1000 • C), an endothermic peak with high intensity was observed at 730 • C, which was accompanied with weight loss of 6.87% on the TGA curve. This peak and weight loss can be explained by decomposition of the CEM I 42.5R aluminate phase, i.e., portlandite decomposition [34][35][36], dehydroxylation of the calcium aluminate and the alumina hydrates and the decomposition of the calcite (carbonates) [34][35][36][37]. However, due to the low amount of carbonate mineral calcite in the Portland cement, this process was not visible on the DTA curve.…”
Section: Thermogravimetric and Differential Thermal Analysis (Tga/dta)mentioning
confidence: 99%
“…Regarding the hydration products present on the surface of the coconut fibers, Soriano et al [32] state that the compounds CSH, CAH and hydrated calcium silicoaluminates (CASH) decompose until 220°C. Moreover, the authors reported that the CH is decomposed in the range of 500-550°C.…”
Section: Thermogravimetric Analysis (Tga)mentioning
confidence: 99%